Comparison of Lateral Flow Assay and RT-PCR for Detection of Canine Distemper Virus in Dogs - Joshi, Vedanshee R.; Bhanderi, Bharat B.; Nimavat, Vipul R.; Jhala, Mayurdhvaj K.; Desai, Dhruv N. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was focused on comparing lateral flow assay (LFA) and one-step RT-PCR for detection of Canine distemper virus (CDV) in dogs. Total of 74 swab (38 nasal and 36 conjunctival) samples from 23 CD suspected dogs were collected. Detection of CDV was performed by LFA using quickVET Rapid test kit and molecular detection by one-step RT-PCR targeting N gene. Based on the test result, sensitivity and specificity were calculated. The prevalence of CD detected by LFA and RT-PCR were 69.56% and 73.91% respectively among dogs.. All the dogs positive for CDV by LFA were also positive by RT-PCR, including one more dog. Comparative analysis of RT-PCR and LFA using sample-wise positivity revealed that relative sensitivity and specificity of LFA considering RT-PCR as the Gold standard test were 66.66% and 100%, while overall agreement between the two assays was 77.03%. For diagnosis of CD in dogs, RT-PCR proved to be a better test than LFA. However, the inherent advantages associated with field tests like LFA and its considerable sensitivity and specificity can be useful and adopted for field-level diagnosis.